Sperm maturation and capacitation in the open thelycum shrimp Litopenaeus (Crustacea: Decapoda: Penaeoidea) - Alfaro Montoya, Jorge (2007)
Transmission electron microscopy was applied to sperm removed from males and females belonging to Litopenaeus vannamei, L. stylirostris and L. occidentalis. It was discovered that a region named filamentous meshwork (FM), located between the nucleus and the hemispherical cap, develops differently in these three closely related species. In L. vannamei, the FM is synthesized in the male reproductive system, but seems to complete its formation after mating. In L. stylirostris, the FM region was not present in spermatophores collected from males or in sperm from the thelycum. In L. occidentalis, the FM region is fully developed in male sperm. It is suggested that completion of the FM is required for acrosome maturation, and the process continues after mating in some species of Litopenaeus. In vitro induction of the acrosome reaction in sperm from males and females of L. occidentalis demonstrated for the first time that reactivity is significantly superior in sperm cells that have been attached to the open thelycum for some hours, as compared to sperm in males (prior to transfer). This finding suggests that matured sperm cells of L. occidentalis become capacitated to react against egg water after mating. © 2007 Elsevier B.V. All rights reserved.